Vegetable ivory - the Beja Botanical Museum photo collection - Carvalho, Luis; Fernandes, Francisca; Nozes, Paula; Albquerque, Sara; Nunes, Fátima (Ethnobotany Research and Applications, 2023)
Vegetable ivory is a raw material used to make small objects, such as buttons, adorns for personal use or home decorations. It comes mainly from the seed endosperm of species belonging to the genus Phytelephas Ruiz & Pav.. The collection of Beja Botanical Museum includes a set of historical photos that show all the stages of vegetable ivory processing from seed to buttons, allowing us to have a more complete understanding of the raw materials and technologies used by this industry in the early 1930’s.